2018
DOI: 10.1155/2018/3878960
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Lauromacrogol Foam Sclerotherapy for the Treatment of Acute Airway Compression Caused by Lymphatic Malformations in Infants

Abstract: Management of LMs still remains a challenge especially for those suffering from complications such as acute airway compression. In this study, we retrospectively evaluated the efficacy and safety of percutaneous lauromacrogol foam sclerotherapy for the patients with acute airway compression caused by lymphatic malformations (LMs) in infants. Five cases of infants with acute airway compression caused by LMs were treated with lauromacrogol foam sclerotherapy in the radiology department from February 2013 to Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Other studies showed that sclerotherapy was more effective in macrocystic LMs compared to microcystic or mixed LMs [ 15 , 37 ]. This could explain the good clinical outcomes in the case series of Wang et al, where all five patients had macrocystic LMs [38] . Although in the present study one patient with a microcystic LM started experimental systemic therapy early, no significant differences were found, probably due to the small patient population and the large subset of mixed LMs in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies showed that sclerotherapy was more effective in macrocystic LMs compared to microcystic or mixed LMs [ 15 , 37 ]. This could explain the good clinical outcomes in the case series of Wang et al, where all five patients had macrocystic LMs [38] . Although in the present study one patient with a microcystic LM started experimental systemic therapy early, no significant differences were found, probably due to the small patient population and the large subset of mixed LMs in this study.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent manuscript, Hou et al 16 described their experience of POL sclerotherapy in 47 patients with VMs and reported a poor outcome for only 2/47 patients. POL sclerotherapy of LMs has been reported in only a few series and rarely in head neck lesions 14 , 17 , 24 . Yamaki et al 17 described a series of 32 LMs treated with polidocanol sclerotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Polidocanol (hydroxy-polyethoxy-dodecane -POL), a synthetic long-chain fatty alcohol, is a liquid surfactant with endothelial cytolytic properties and has mainly been used for venous malformations. Polidocanol injection is painless, does not induce necrosis if injected intradermally and rarely produces allergic or inflammatory reactions [13][14][15][16][17] . Recently, it has also been proposed for lymphatic ones even though it has been investigated in only a limited number of studies based on small samples, including several sites and not focused only on head and neck cases 14,17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations